New insights into the pharmacokinetics of vancomycin after oral and intravenous administration: an investigation in beagle dogs - Sauter, Max; Uhl, Philipp; Meid, Andreas; Mikus, Gerd; Burhenne, Jürgen; Haefeli, Walter E. (Journal of pharmaceutical sciences, 2020)
Intestinal absorption of orally administered peptides is often negligible because one or more key requirements for successful absorption (water solubility, peptic resistance, mucosal permeation) are not met. Due to its high water solubility and stability in the gastro-intestinal tract, vancomycin is an ideal model peptide for evaluating the factors influencing the critical step of mucosal permeation. Therefore, to support formulation development for the systemic oral delivery of peptide therapeutics, we investigated the pharmacokinetics of vancomycin in beagle dogs after intravenous and oral administration comparing enteric encapsulated drug to the drug in solution, which revealed mean absolute bioavailabilities of 0.27% and 1.66%, respectively. Additionally, in depth pharmacokinetic analyses of intravenously administered vancomycin revealed a deep compartment slowly releasing the compound over many hours into the blood.
Gesehen am 19.03.2021